Perlindungan Hukum Debitur Melalui Gugatan Perdata atas Lelang Sewenang-Wenang oleh Kreditur dalam Perjanjian Hak Tanggungan - Yoga Pratama, Ari; Indra Muhtar, Muhammad; Dian Asha, Wafiyatun; Dwi Jayanti, Kharin (UNIVERSITAS SERAMBI MEKKAH, 2024)
Indonesia is a legal state, a legal state is a state that carries out all its rights and obligations in accordance with the constitution. It is stated in article 28D paragraph 1 which states that